Telemedicine and the current opportunities for the management of oncological patients in Peru in the context of COVID-19 pandemic. (January 2021) - Montenegro, Paola; Pinillos, Luis; Young, Frank; Aguilar, Alfredo; Tirado-Hurtado, Indira; Pinto, Joseph A.; Vallejos, Carlos
Abstract: COVID-19 pandemic is the more challenging public health emergency of the century, producing the collapse of health systems and unprecedented levels of morbidity and mortality around the world, especially in low resource settings. Patients with chronic diseases are the most affected, not only due to the high susceptibility to SARS-CoV-2 infection but also due to the decrease in opportunities for timely care. In this dark landscape, telemedicine, before limited to very specific scenarios, has become one of our main tools to manage cancer patients, particularly in Latin America where COVID-19 has had a strong impact on the public health. Telemedicine can provide rapid access to specialized cancer care in a scenario complicated, reducing the exposure of patients and healthcare personnel to the SARS-CoV-2. In this review, we would like to share our experience and our workflow using telemedicine at Oncosalud-AUNA, a private clinic in Peru.